Walking the Ocean with Papoesche Zeerovers: Historical Narratives in Navigation, Maritime, and Biak Identity in Indonesia - Muhammad Fadland (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2026)
Abstrak This study examines the construction of maritime identity of the Biak tribe in Papua through the term Papoesche Zeerovers. This designation appeared in Dutch colonial archives to describe a group of pirates from Papua. With a qualitative approach and ethnohistorical methods, this study seeks to reconstruct the role and strategic position of the Biak tribe in the traditional shipping network of the Southwest Pacific region, as well as unravel colonial perceptions that distort their historical reality. The study's findings show that the Biak tribe has a complex marine navigation system, controls shipping lanes to Maluku and the coast of Papua New Guinea, and plays a vital role in cultural, economic, and maritime political exchanges. The label of pirates (zeerovers) pinned by the colonial government tended to be political and reductive, ignoring the local context of the shipping and resistance actions. Thus, this article emphasizes the importance of deconstructing colonial terms in rewriting Indonesia's maritime history from a local perspective and re-elevating the identity of the Biak tribe as formidable and autonomous sailors-navigators.